What's Driving Private Investment in Malaysia? : Aggregate Trends and Firm-Level Evidence - Unteroberdoerster, Olaf.; Guimaraes, Roberto (Washington, D.C. : International Monetary Fund, 2006)
Private sector investment has been a key source of growth in Malaysia over the last three decades, but after an unprecedented decline in the wake of the Asian crisis it has remained sluggish in recent years. Using aggregate and firm-level data, this paper aims to explain these trends and their implications for Malaysia's investment and growth outlook. Aggregate data point to sustained overinvestment in the years prior to the Asian crisis and the role of shifts in investor perceptions as important determinants of the recent decline in private investment. Meanwhile, firm-level data suggest that low profitability, along with financing constraints affecting smaller firms and those in the services sector, has also been important.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet